Super Strengthening Nano‐Polycrystalline Diamond through Grain Boundary Thinning. (2nd March 2023) - Yao, Mingguang; Shen, Fangren; Guo, Dezhou; Zhang, Hua; Zhai, Chunguang; Shang, Yuchen; Dong, Jiajun; Zhao, Yuanlong; Liu, Zhaodong; Li, Zhipeng; Li, Haixin; Li, Hongdong; et al.
Abstract: Introducing nanostructures into diamonds is quite appealing for the synthesis of superhard materials with superior properties. However, as the grain size decreases to nanoscale, grain boundary effects become crucial yet complicated in the nanopolycrystalline diamond (NPD), making it challenging to tailor nanostructures. Here, atomistic simulations are combined with experiment to demonstrate a strengthening strategy for the sintered NPD by introducing thin amorphous grain boundary (AGB). The additive of small percentage of fullerene into precursors during sintering can significantly reduce crushed amorphous‐like nanodomains in diamond nanocrystals, leading to the formation of thin AGB. Such sintered NPD exhibits a significant hardness and fracture toughness enhancement, exceeding that of single crystal diamonds. These atomistic simulations show that upon straining the plastic deformation, crack initiation and propagation in NPD is AGB thickness dependent, and thin AGB can reduce crack nucleation and block crack propagation, well explaining the experimental observations. This study indicates that grain boundary modulation provides a promising approach for rational designs of high‐performance superhard materials with desired high strength. Abstract : Modulating grain boundary properties to improve materials' performance remains a challenging task for polycrystalline materials with strong covalent bonds. Here, nanopolycrystalline diamond (NPD) is selected as the prototype to illustrate the underlying mechanisms of the grain boundary effects. More interestingly, how to modulate and enhance the mechanical properties of NPD via tailoring the grain boundary is shown.